Synergistic, additive and antagonistic effects of fruit mixtures on total antioxidant capacities and bioactive compounds in tropical fruit juices - da Silva Pereira, Ana Carolina; Wurlitzer, Nedio Jair; Dionísio, Ana Paula; Lacerda Soares, Marcia Valéria; Rocha Bastos, Maria do Socorro; Elesbão Alves, Ricardo; Montenegro Brasil, Isabella (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
The objective of this work was investigate the synergistic, additive and antagonistic effects of fruit mixtures on total antioxidant capacities and bioactive compounds in tropical fruit juices, and optimize its formulation by the response surface methodology based on the responses: total polyphenols (TP), total antioxidant capacity (TAC), ascorbic acid content and sensorial acceptance. Camu-camu, acerola and acai were the major factors that influenced the antioxidant potential of the juice; and the yellow mombin showed a positive effect on the acceptance of the tropical juice. It was observed an antagonistic effect between acerola and camu-camu for the TAC response. The optimum formulation obtained was 20% acerola, 10% camu-camu, 10% yellow mombin, 10% cashew apple and 10% acai, which was responsible for a response of 155.46 mg.100 g-1 of ascorbic acid, 103.01 mg of GAE.100 g-1 of TP, 10.27 μM Trolox g-1 of TAC and approximately 6.1 of acceptance. El objetivo de este trabajo fue investigar los efectos sinérgicos, aditivos y antagónicos de mezclas de diferentes frutas tropicales en la capacidad antioxidante total (TAC) y compuestos bioactivos presentes en los jugos mixtos, y optimizar su formulación por la metodología de superficie de respuesta basado en las evaluaciones de: polifenoles totales (TP), capacidad antioxidante total (TAC), contenido de ácido ascórbico y la aceptación sensorial. Camu-camu, acerola y acai fueron las frutas que más influyeron en el potencial antioxidante del jugo mixto; y el jobo mostró un efecto positivo en la aceptación del jugo mixto tropical. Se observó un efecto antagónico entre acerola y camu-camu para la TAC. La formulación óptima obtenida contenía 20% acerola, 10% de camu-camu, 10% el jobo, 10% de manzana de marañón y 10% de acai, la cual ha proporcionado contenidos medio de 155,46 mg.100 g-1 de ácido ascórbico, 103,01 mg de GAE.100 g-1 de TP, 10,27 mM Trolox g-1 de TAC y aproximadamente 6.1 de aceptación sensorial.